2021
DOI: 10.24996/ijs.2021.62.4.25
|View full text |Cite
|
Sign up to set email alerts
|

Peristaltic Transport of Power-Law Fluid in an Elastic Tapered Tube with Variable Cross-Section Induced by Dilating Peristaltic Wave

Abstract: The peristaltic transport of power-law fluid in an elastic tapered tube with variable cross-section induced by dilating peristaltic wave is studied. The exact solution of the expression for axial velocity, radial velocity, stream function, local shear stress, volume of flow rate and pressure gradient are obtained under the assumption of long wavelength and low Reynolds number. The effects of all parameters that appear in the problem are analyzed through graphs. The results showed that the flux is sinusoidal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…4.2. The pressure gradient ( ∂p ∂x ) Figure (8)(9)(10)(11)(12) shows the behavior of the pressure gradient ( ∂p ∂x ) for different values such that the curvature parameter, the flow rate, amplitude ratio parameter, the non-Newtonian fluid number and the Hartman number. These graphs show that the pressure gradient oscillates along the side walls of the tube.…”
Section: The Velocity Profilementioning
confidence: 99%
See 1 more Smart Citation
“…4.2. The pressure gradient ( ∂p ∂x ) Figure (8)(9)(10)(11)(12) shows the behavior of the pressure gradient ( ∂p ∂x ) for different values such that the curvature parameter, the flow rate, amplitude ratio parameter, the non-Newtonian fluid number and the Hartman number. These graphs show that the pressure gradient oscillates along the side walls of the tube.…”
Section: The Velocity Profilementioning
confidence: 99%
“…Recent interest in the peristalsis phenomenon can be attributed to engineering and medical uses. Embryonic development, the transport of oocytes and embryos, and the pulsation of blood arteries are all examples of peristaltic flow in living systems [1,2,3,4,5,6,7,8,9,10,11,12,13]. One advantageous component in engineering applications is turbo machines and aircraft wings.…”
Section: Introductionmentioning
confidence: 99%
“…Jaffrin [7] discussed inertia and streamline curvature effects on peristaltic pumping. Gupta and Seshadri [8] ENGINEERING MODELLING 35 (2022) 2, [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] analyzed peristaltic pumping in non-uniform tubes. Hariharan et al [9] studied the peristaltic transport of power law and Bingham fluid in a diverging tube with different wave forms as sinusoidal, multi-sinusoidal, triangular, trapezoidal and square waves and employed Fourier series to get the equations and results.…”
Section: Introductionmentioning
confidence: 99%
“…Pandey and Tiwari [21] studied the swallowing of Casson fluid through the oesophagus under the influence of peristaltic waves of varying amplitude. Murad and Abdulhadi [22] discussed peristaltic transport of power-law fluid in an elastic tapered tube with variable cross-section induced by dilating peristaltic wave and showed that the flux is sinusoidal in nature.…”
Section: Introductionmentioning
confidence: 99%